Shortage of Appendicular Skeletal Muscle is an Independent Risk Factor for Mortality in Peritoneal Dialysis Patients. Issue 1 (January 2017) - Jin, Sanli; Lu, Qian; Su, Chunyan; Pang, Dong; Wang, Tao
Background: Limited data are available on clinical outcomes among peritoneal dialysis patients with shortage of appendicular skeletal muscle (ASM). In this study, we tested the hypothesis that the shortage of ASM is an independent risk factor for mortality in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: Adult patients undergoing CAPD between March and August 2007 in a single center in China were recruited in this prospective cohort study. Body composition, protein/energy intake, clinical, and biochemical data were collected at baseline, 6 months, and 12 months. End points were all-cause mortality by 12 September 2014. The mean follow-up time was 60.21 (± 24.45) months (11.00 – 89.00). Results: Compared with the baseline, the mean value of ASM in CAPD patients decreased at 12 months (19.40 ± 5.60 vs 21.85 ± 6.14, p < 0.001). According to the estimation of patient survival by Kaplan-Meier, patients with a shortage of ASM had a worse survival rate than those with normal ASM (χ 2 = 16.588, p < 0.001). In the Cox's proportional hazards model, patients' survival was independently associated with a shortage of ASM (hazard ratio [HR] = 2.318, p = 0.024, 95% confidence interval [CI] = 1.116 – 4.812). Standard daily protein intake (stDPI) and standard daily energy intake (stDEI) in patients with a shortage of ASM were significantly lower than those in patients with normal ASM in the first follow-up year ( t = 2.067, p = 0.041; t = 3.673, p = 0.001). Conclusions: A shortage of ASM is an independent risk factor for mortality in CAPD patients. Further studies are needed to demonstrate that nutritional intervention helps with improving muscle mass and, consequently, the survival of CAPD patients.